Investigation of Partial Discharges at the High Voltage Electric Motor Bars - Dauksys, Gediminas; Jonaitis, Audrius; Gudzius, Saulius; Morkvenas, Alfonsas (Elektronika ir Elektrotechnika, 2016)
It is well known the use of on-line partial discharge (PD) measurements as an indicator of stator winding insulation condition. The scheduled PD measurements could be used as a test to evaluate the quality of the equipment. The test results could help to diagnose the insulation problems in motors and generators for corresponding action before failure occurs. Although a number of PD measurement methods exists, but the tests results of on operating rotating machines can be influenced by conditions such as humidity, temperature, terminal voltage, and load. This paper describes the development of PD imitation mathematical model in stator insulation. The experimental investigation with physical model was performed for adequacy assessment. The capacitive sensor was used for PD online monitoring. DOI: http://dx.doi.org/10.5755/j01.eie.22.2.6983